The Moderation Effects of Task Complexity on Professional Skepticism, Inter-Agency Cooperation, and Tax Auditors’ Performance Relationship - Ahmad, Mohmad Hazar; Mustapha, Mazlina; binti Yusri, Yusniyati; Binti Kharuddin, Saira (International Journal of Economics, Management and Accounting, 2026)
This study examines the influences of professional skepticism and inter-agency cooperation on tax auditors’ performance based on the attribution theory. Using expectancy theory, the research further explores the moderating effects of task complexity on the relationship between professional skepticism, inter-agency cooperation, and tax auditors’ performance. A quantitative approach was adopted, employing survey questionnaires distributed to tax auditors from the Inland Revenue Board of Malaysia (IRBM) and the Royal Malaysian Customs Department (RMCD). The data underwent analysis using IBM-SPSS-AMOS version 21 for Structural Equation Modelling (SEM) statistical analysis. The results reveal that both professional skepticism and inter-agency cooperation impact on tax auditors’ performance. Moreover, task complexity was found to moderate the relationships between professional skepticism, inter-agency cooperation, and tax auditors’ performance. It is important to note that this study focused solely on the influence of professional skepticism, inter-agency cooperation, and task complexity on tax auditors’ performance, without testing other internal and external factors. This study contributes to theoretical implications in the field of taxation, particularly within tax auditing, by offering empirical evidence on the effects of internal and external factors on tax auditors’ performance, along with the moderating influence of task complexity. The findings provide valuable insights for the IRBM and RMCD, emphasizing the significance of professional skepticism, inter-agency cooperation, and task complexity in enhancing tax auditors’ performance. Notably, the uniqueness of this study lies in the researchers’ exploration of the synergy between direct and indirect taxes to deepen the understanding of factors affecting tax auditors’ performance.